Role of Pcf11 post-translational modifications in gene expression - Volanakis, A (2016)
mRNA export is one of the major steps in the regulation of gene expression as it provides the link between gene transcription in the nucleus and mRNA translation in the cytoplasm. Efficient export of mRNAs requires the formation of mRNPs at the sites of transcription consisting of the mRNA in complex with export and transcription factors. Formation of the mRNPs is tightly coupled with the co-transcriptional processes of capping, splicing and polyadenylation of the transcript. Our work focuses on the core termination factor Pcf11, a component of the Cleavage Factor II complex in mammals. Pcf11 is an essential protein in yeast and it has been shown to participate in 3' end formation of the transcript (cleavage and polyadenylation) as well as in the release of RNA polymerase II from the DNA. We discovered the phosphorylation of 2 residues in the CID domain of human Pcf11. The CID domain is responsible for the interaction of the factor with the CTD domain of RNA polymerase II. Furthermore, we identified Wnk1 as the kinase responsible for this phosphorylation. Our experiments show that phosphorylation of Pcf11 CID by Wnk1 disrupts its interaction with RNA polymerase II. Further analysis of Wnk1 and its role in the nucleus revealed that this kinase participates in mRNA export. We propose a model, where phosphorylation of Pcf11 CID by Wnk1 is required for proper mRNP assembly and release from the site of transcription. Our data identify a new role for Wnk1 in gene expression regulation through mRNA export and new insights into the cross-talk between transcription termination and mRNA export.